Development of individual competencies and team performance in interprofessional ward rounds: results of a study with multimodal observations at the Heidelberg Interprofessional Training Ward - Mitzkat, Anika; Mink, Johanna; Arnold, Christine; Mahler, Cornelia; Mihaljevic, André L.; Möltner, Andreas; Trierweiler-Hauke, Birgit; Ullrich, Charlotte; Wensing, Michel; Kiesewetter, Jan (Frontiers in Medicine, 2023)
Interprofessional training wards (IPTW) aim to improve undergraduates interprofessional collaborative practice of care. Little is known about the effects of the different team tasks on IPTW measured by external assessment. In Heidelberg, Germany, interprofessional ward rounds are a central component of the IPTW. The aim of this study was to evaluate individual competencies and team performance shown in ward rounds. Observations took place in four cohorts of four nursing and four medical undergraduates each at the beginning (t0) and the end (t1) of the placement on the IPTW using the IP-VITA instrument for individual competencies (16 items) and team performance (11 items). Four hypotheses were formulated for statistical testing with linear mixed models and correlations. Sixteen nursing and medical undergraduates each were included. There were significant changes of mean values between t0 and t1 in individual competencies (Hyp.1). They were statistically significant for alle three sum scores “Roles and Responsibilities”, Patient Centeredness” and “Leadership”. In terms of team performance (Hyp.2), there was a statistically significant change of mean values in the sum score “Roles and Responsibilities” and positive trends in the sum scores “Patient Centeredness” and “Decision making/Collaborative Clinical Reasoning”. Analysis of differences in the development of individual competencies in the groups of nursing and medical undergraduates (Hyp.3) showed more significant differences in the mean values of the two group in t0 than in t1. There were significant correlations between individual competencies and team performance at both t0 and t1 (Hyp.4). It has been observed that medical undergraduates acquired and applied skills in collaborative clinic reasoning and decision making whereas nursing undergraduates acquired leadership skills. Within the study sample only a small group of tandems remained constant over time. In team performance, the group of constant tandems tended to perform better than the group of random tandems. The aim of IPTW should be to prepare healthcare team members for the challenge of changing teams. Therefore, implications for IPTW implementation could be to develop learning support approaches that allow medical and nursing undergraduates to bring interprofessional competencies to team performance independent of the tandem partner or team.